El impacto de las cuotas obrero patronales respecto de las sentencias del Tribunal Federal de Justicia Administrativa - Pimienta Rodríguez, Martha Julieta (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In order for workers to enjoy social security services, such as housing and medical services, it´s important for employer pays, in the workers’ favor, the social security contributions as per the Mexican Social Security Institute and the National Housing Fund for Workers Institute rules, otherwise, these two independent tax agencies can act against the employer establishing the due debt that may be collect even coercively. It´s true that the employer can defend itself against such debt, either through an administrative recourse or through an administrative federal trial, in either case, the resolution or sentence, respectively, may recognize the debt’s validity or establish its illegality (the last word on the dispute may be said by the administrative federal court o by a superior federal tribunal). This resolution may absolute the tax payer or authorize the above mention independent tax agencies to replace. In the first case, currently, the employer is debt free, despite the negative affectation on worker´s´ rights, while in the second case, the employer must pay the replaced debt. Under the premise that the workers’ rights must be save when is not in dispute the existence of the working relation, this thesis proposes, first, that the workers, whose rights may be affected, to be called to trial in order to be able to defend themselves, through a representative of their choice.

A fin de que los trabajadores gocen de los beneficios de los derechos sociales de salud y vivienda, es importante que el patrón cumpla con su obligación de enterar las cuotas obrero patronales y de aportaciones de vivienda, con la consecuencia que, de no hacerlo, el Instituto Mexicano del Seguro Social y el Instituto del Fondo Nacional de Vivienda para los Trabajadores en cuanto organismos fiscales autónomos, respectivamente, puedan liquidarlas. Frente a esa liquidación, el patrón puede acudir a, entre otros medios de defensa, el juicio contencioso administrativo ante el Tribunal Federal de Justicia Administrativa (denominación aplicable a partir de la reforma al artículo 73, fracción XXIX, inciso H) de la Constitución Política de los Estados Unidos Mexicanos, publicada en el Diario Oficial de la Federación el 27 de mayo de 2015, antes Tribunal Federal de Justicia Fiscal y Administrativa), el cual, se resuelve con la sentencia definitiva que al efecto se emita, que puede ser, esencialmente, reconociendo la validez del acto impugnado, declarándolo nulo para efectos o nulo lisa y llanamente. Cuando en el juicio se declara la nulidad lisa y llana, por vicios de fondo, de la cédula de liquidación por omisión total o parcial del entero de cuotas obrero patronales o de aportaciones de vivienda, implica que la autoridad emisora no pueda purgarlo y que el patrón quede liberado totalmente de pagar esas cuotas y aportaciones; a pesar de las afectaciones que se causan a los trabajadores.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2018-1539; Juicio; IMSS; Aportaciones; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6164